Competition intensity and its above- and below-ground components in two contrasting wetland plant communities. - Twolan-Strutt, Lisa. (University of Ottawa (Canada), 1994)
I used a field experiment to measure total competition intensity and its above- and below-ground components in two wetlands that represent extremes in habitat productivity: an infertile sandy shoreline and a fertile bay. Transplants of Lythrum salicaria and Carex crinita were grown with no neighbours, with roots of neighbours only and with all neighbours; their growth rates were used to estimate competition intensity. The experiment was carried out to answer the following main questions: (1) Is there a difference in total, above- and below-ground competition intensity in two wetlands that differ in standing crop? (2) Is there an effect of standing crop on total, above- and below-ground competition intensity when the data from the two wetlands are combined? Both total and above-ground competition intensity were found to be greater in the high standing crop wetland but below-ground competition did not differ between wetlands (CI$\rm\sb{TOTAL}$: p 0.00001, CI$\rm\sb{ABOVE}$: p = 0.0013 CI$\rm\sb{BELOW}$: p = 0.58). Mean total competition increased from 0.16 to 0.43, the above-ground component increased from $-$0.063 to 0.21 and the below-ground component was close to 0.20 in both wetlands. Total and above-ground competition intensity was significantly affected by standing crop in the wetlands studied but below-ground competition intensity was not (CI$\rm\sb{TOTAL}$: p = 0.0001, CI$\rm\sb{ABOVE}$: p = 0.0001, CI$\rm\sb{BELOW}$: p =0.89). The result that competition was predominantly below-ground in the low standing crop wetland supports previous work in agricultural pot experiments (Wilson 1988) and terrestrial field studies (Wilson and Tilman 1991, Putz and Canham 1992, Wilson and Tilman 1993, Wilson in press). The result that root and shoot competition were roughly equal in the high standing crop wetland is not typical of past studies. (Abstract shortened by UMI.)
Keywords: Biology, Botany.